Effects of Growth Medium and Inoculum Size on Pharmacodynamics Activity of Marbofloxacin against Staphylococcus aureus Isolated from Caprine Clinical Mastitis - Augusto Matías Lorenzutti; Manuel Ignacio San Andrés-Larrea; Emilio Fernández-Varón; María del Pilar Zarazaga; Ana María Molina-López; Juan Manuel Serrano-Rodríguez (MDPI AG, 2021)
Staphylococcus aureus (S. aureus) is an important pathogen that causes clinical mastitis in goats and produces infections difficult to cure. Different antimicrobials as fluoroquinolones have been used against S. aureus. However, the studies developed to evaluate the bacterial drug interaction only have used the MIC as a single reference point with artificial growth media. The aims of this study were to describe the effect of marbofloxacin on S. aureus isolated from mastitis goats' milk by different approaches as the minimum inhibitory and bactericidal concentrations (MIC and MBC) in cation adjusted Mueller-Hinton broth (CAMHB), serum and milk of goats at two inoculum sizes of 105 and 108 CFU/mL, the determination and analysis of the time kill curves (TKC) by non-linear mixed effect models in each growth medium and inoculum size, as well as the estimation of their pharmacokinetics/pharmacodynamics (PK/PD) cutoff values. The results obtained indicate that MIC values were higher and increases 2,4-fold in serum and 3,6-fold in milk at high inoculum, as well as the EC50 values determined by each pharmacodynamics model. Finally, the PK/PD cutoff values defined as fAUC24/MIC ratios to achieve clinical efficacy were highly dependent on inoculum and growth medium, with median values of 60-180, especially at high inoculum in milk, suggesting that further studies are necessary to evaluate and optimize the best therapeutic strategies for treating S. aureus in lactating goats.